The malady of low global interest rates - Tanweer Akram (Levy Economics Institute of Bard College, 2015)
Long-term interest rates in advanced economies have been low since the global financial crisis. However, in the United States the Federal Reserve could begin to hike its policy rate, the federal funds target rate, before the end of the year. In the United Kingdom, the Bank of England could follow suit. What is the outlook for global long-term interest rates? What are the risks around interest rates? What can policymakers do to cure the malady of low interest rates? It is argued that global interest rates are likely to stay low in the remainder of this year and the first half of next year due to a combination of domestic and international factors, even if a few central banks gradually begin to tighten monetary policy. The cure for this malady lies in proactive fiscal policy and measures to support job growth. Boosting effective demand and promoting higher wages and real disposable income would help lift inflation rates close to their targets and raise long-term interest rates.
Keywords: E43; E50; E60; 330; Government Bond Yields; Global Interest Rates; Long-Term Interest Rates